Physiological and anthropometric characteristics of female football athletes: A study literature review - Irana Mery Alviana; RD. Devy Citra Pratiwi; Naufal Dzaki Hartianto; Nur Luthfiatus Solikah (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
Indonesian women's football began to develop in 1969 with the formation of the first women's football team. It then began to receive more attention in 2019 with the official competition, namely the women's league 1 (one) created by the PSSI. However, there has been no follow-up women's league activities in Indonesia since the pandemic. The development of Indonesian women's football has not been accompanied by a sustainable coaching system and adequate institutional support at the school, club, and national levels. The availability of scientific data on the physiological and anthropometric characteristics of female players is still limited. Understanding the physiological and anthropometric characteristics of players is crucial in the process of screening potential, developing, training, and coaching athletes to support optimal performance. The purpose of this literature review is to analyze the latest findings related to the physiological and anthropometric characteristics of female soccer players as a basis or reference to support the selection process, athlete development, and the development of appropriate and effective data-based training methods to improve women's soccer performance at the national and international levels. This study uses a literature review approach with a narrative review type. The sources of the articles analyzed were obtained from online databases such as Google Scholar, PubMed, ScienceDirect, Web of Science with keywords combined using Boolean operators namely AND, OR, and NOT. The results of the literature review show physiological and anthropometric characteristics that vary across age groups and player positions. A player's physical abilities and body proportions greatly support performance on the field. Therefore, this literature review can be used as a reference or relevant norm in the selection process, coaching, and training tailored to the profile of each athlete to improve women's soccer performance in Indonesia.